The Effect of Growth Regulator Substance and Growing Media on The Growth of Shoot Cuting Coffea arabica L. - Aditya Hani; Riskyia Amalia Muhyidin (Jurnal Agroforestri Indonesia, 2020)
Coffee can be propagated vegetatively, namely by cuttings. One of the factors that can affect the success of coffee cuttings is the use of growth regulators (ZPT) and the right type of planting medium. This study aims to determine the concentration of growth regulators and the type of planting medium that gives the best growth in Arabica coffee cuttings (Coffea arabica L.). The research was conducted at the nursery of the Agroforestry Research and Development Center in Cijeungjing, Ciamis Regency. The experiment was conducted from August to November 2019. The experiment used a factorial randomized block design (RBD) consisting of two factors. The main factors were planting media: cocopeat, husk charcoal, soil; the second factor was the concentration of auxin regulators with active ingredients (active ingredients: naphthalene acetic and naphthalene acetic amid): 0 ppm, 1,000 ppm, 2,000 ppm, 3,000 ppm. The results showed that the interaction between the treatment of planting media and the provision of growth regulators only gave a significant difference in the number of secondary root parameters. The single factor effect of ZPT dose did not provide significant differences in each parameter. Single factor of soil media resulted in significant differences in the parameters of the percentage of root cuttings, root dry weight and percentage of live cuttings. Based on the results of this study, the use of soil growing media resulted in the best percentage of cuttings compared to other growing media.